Children's perception of the fairness of parental preferential treatment and their socio-emotional well-being. - Matrido, Nerriza and Keith Remegio
This study was undertaken to demonstrate the relationships between perceived fairness of parental preferential treatment and children?s self-esteem, social adjustment and the quality of sibling relationship. Respondents of the study included 48 children who reported to have experienced differential treatment from their mother and 49 children who reported to have observed differential treatment from their fathers. The design of the study was correlational. Questionnaires were utilized to measure the children?s self-esteem, social judgment and the quality of sibling relationship. Spearman rank correlation was used to examine the relationships between the variables in the study. Results showed that there exists a relationship between perceived fairness of parental preferential treatment and children?s quality of sibling relationship for both mother and fathers. That is, the more fair the perception of parental preferential treatment, the better the quality of sibling relationship. However, the expected relationships between perceived fairness of parental preferential treatment and children?s self-esteem and social adjustment were not supported.